Miskonsepsi Pengerjaan Operasi Deret Aritmatika di Pgmi-3 Universitas Islam Negeri Sumatera Utara - Fenika Ardiyani; Rora Rizki Wandini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to identify misconceptions that may occur in working on arithmetic series operations among PGMI-3 students at UIN North Sumatra. Arithmetic series are an important topic in mathematics that is often used in various scientific contexts. However, misconceptions in understanding and performing arithmetic series operations can be an obstacle to strong understanding and problem-solving abilities. This research uses survey and test methods to identify misconceptions that generally arise when PGMI-3 students work on arithmetic series operations. The research results show that there are several misconceptions involving understanding the general formula for arithmetic series, calculating the nth term, and adding terms in a series. Most of these misconceptions are related to an inaccurate understanding of the basic concepts of arithmetic series. This study also attempts to identify factors that may contribute to these misconceptions, including teaching methods, teaching materials, and students' educational background. The results provide important insights for the development of curricula and teaching approaches that are more effective in understanding arithmetic series operations. With a better understanding of the misconceptions that may arise in working on arithmetic series operations, appropriate action can be taken to overcome this problem and help PGMI-3 students at UIN North Sumatra develop a better understanding of mathematics. This research also has implications in the broader context of mathematics education in Indonesia.